Review of full truckload transportation service procurement - Jothi Basu, R.; Subramanian, Nachiappan; Cheikhrouhou, Naoufel (Taylor & Francis, 2015)
This study was conducted to review the literature on full truckload (FTL) transportation service procurement and to identify the gaps from the perspectives of researchers and practitioners. FTL procurement in particular was reviewed because it is encountered more than others forms of procurement in freight movement, and it involves numerous challenges. A framework was developed to provide a systematic review of the literature, the findings of which are discussed in detail. Some key findings include the simplistic assumption of demand patterns, limited focus on non-price variables, a limited number of case studies, less consideration of sustainability aspects, and a lack of detailed studies on emerging economies.